Mimesis - między udawaniem a referencją - Mitosek, Zofia (Przestrzenie Teorii, 2007)
This study reformulates the old problem of mimesis in the spirit of pragmatics. It treats similarity as as a subjective-objective relation. Comparison of the conception of formal mimetism and literature as pretending of actual acts of speech leads to a conclusion on the asymmetry of these two modern applications of the category of mimesis. The first one attempts at restricting its use, the second attempts at globalisation, a kind of which is pragmatisation. Conception of mimesis as pretending strengthens the objective characterisation of categories. The function of convention is emphasised, which determines either the mimetic or referential reading of a text, which becomes particularly important in the reading of documentary and paradocumentary literature where we have to do with a permanent asymmetry of the sender's expectations and of the recipient's reactions. Attempts at defining mimesis in terms of cognitivist theories are conducive to pragmatisation of categories where the mental effects of a literary representation are involved, and the similarity is defined as closeness of a text and perceptual schemes located in the recipient's brain. All these processes lead to the questioning of mimesis as a palpable property in the structure of the text, stressing the reader's and the reading's role in the constitution of the mimetic effect.